Matchup eaudiobook - Child, Lee (Simon & Schuster Audio, 2017)
This "highly recommended" ( Publishers Weekly , starred review) collection edited by New York Times bestselling author Lee Child pairs the beloved characters of twenty-two internationally bestselling writers in "a must-read for fans of the thriller genre" ( The Real Book Spy ). The incredible follow-up to FaceOff features twenty-two of the world's bestselling and critically acclaimed thriller writers pairing their series characters in an eleven-story anthology curated by the International Thriller Writers (ITW). MatchUp takes the never-before-seen bestseller pairings of FaceOff and adds a delicious new twist: gender. "Think Dancing With the Stars , but with mysteries" ( Booklist ) as eleven of the world's best female thriller writers from Diana Gabaldon to Kathy Reichs to Charlaine Harris are paired with eleven of the world's best male thriller writers, including John Sandford, C.J. Box, and Nelson DeMille, among others. "This box holds a chocolate or two that will be to everyone's liking" ( Kirkus Reviews ). In these innovative stories, their beloved protagonists, Lee Coburn, Joe Pickett, and Jack Reacher—just to name a few—team up to unnerve and satisfy thriller fans worldwide. All of the contributors are ITW members, and the project is edited by ITW member and #1 New York Times bestselling author Lee Child. The lineup includes: Sandra Brown's Lee Coburn vs. C. J. Box's Joe Pickett Val McDermid's Tony Hill vs. Peter James's Roy Grace Kathy Reichs's Temperance Brennan vs. Lee Child's Jack Reacher Diana Gabaldon's Jamie Fraser vs. Steve Berry's Cotton Malone Gayle Lynds's Liz Sansborough vs. David Morrell's Rambo Karin Slaughter's Jeffrey Tolliver vs. Michael Koryta's Joe Pritchard Charlaine Harris's Harper Connelly vs. Andrew Gross's Ty Hauck Lisa Jackson's Regan Pescoli vs. John Sandford's Virgil Flower Lara Adrian's Lucan Thorne vs. Christopher Rice's Lilliane Lisa Scottoline's Bennie Rosato vs. Nelson DeMille's John Corey J.A. Jance's Ali Reynolds vs. Eric Van Lustbader's Bravo Shaw